2019
DOI: 10.1177/1474515119860321
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of angiotensin-converting enzyme inhibitors or beta-blockers and the impact on heart failure hospitalization rates

Abstract: Background: Adherence to evidence-based therapy is essential for optimal management of heart failure. Yet, medication adherence is poor in heart failure patients. The Ascertaining Barriers to Compliance Project decomposed the medication adherence process into initiation, implementation, and discontinuation stages, but electronic monitoring-based adherence analyses usually do not consider this process. Aims: The aim of this study was to describe individual-patient patterns of medication adherence from electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In addition, the QoL and rehospitalization due to CHF exacerbation were also improved, which we considered might be at least partly due to the higher rate of adherence to medications therapy. Indeed, evidence from prior studies also demonstrated that CHF patients with good adherence to medications therapy had lower incidence of rehospitalization and mortality [24][25][26]. However, as presented in Table 2, although patients in the intervention group had higher rates of adherence to medications therapy than in the control group, compared to medications prescribed at discharge, the percentage of patients who continued on these medications therapy declined.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the QoL and rehospitalization due to CHF exacerbation were also improved, which we considered might be at least partly due to the higher rate of adherence to medications therapy. Indeed, evidence from prior studies also demonstrated that CHF patients with good adherence to medications therapy had lower incidence of rehospitalization and mortality [24][25][26]. However, as presented in Table 2, although patients in the intervention group had higher rates of adherence to medications therapy than in the control group, compared to medications prescribed at discharge, the percentage of patients who continued on these medications therapy declined.…”
Section: Discussionmentioning
confidence: 89%